Analisis Rasio Cael Untuk Menilai Tingkat Kesehatan Pada Bank Nasional Yang Diakuisis Investor Asing Pada Periode 2019-2021 - Patuteuogo, Rijul; Paramitha, Melvie (Rifa'Institute, 2023)
Research Analysis of the CAEL Ratio to Assess the Health Level of National Banks Acquired by Foreign Investors in the 2019-2021 Period. This study is entitled